-3x+6=-2x+7

Simple and best practice solution for -3x+6=-2x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+6=-2x+7 equation:


Simplifying
-3x + 6 = -2x + 7

Reorder the terms:
6 + -3x = -2x + 7

Reorder the terms:
6 + -3x = 7 + -2x

Solving
6 + -3x = 7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
6 + -3x + 2x = 7 + -2x + 2x

Combine like terms: -3x + 2x = -1x
6 + -1x = 7 + -2x + 2x

Combine like terms: -2x + 2x = 0
6 + -1x = 7 + 0
6 + -1x = 7

Add '-6' to each side of the equation.
6 + -6 + -1x = 7 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = 7 + -6
-1x = 7 + -6

Combine like terms: 7 + -6 = 1
-1x = 1

Divide each side by '-1'.
x = -1

Simplifying
x = -1

See similar equations:

| -5x+15=-4x+12 | | 3x-14=6x-38 | | 28-(-3)*(-7)= | | 37.5=x^3 | | 5x-6=-x+6 | | 22x+4+35x+5=180 | | 1-x^2=-7-3 | | (x-3/4)^2 | | 2x+23+2x+23=8x | | 4.5*X=13.5 | | 360=(6x-4)+(2x+8)+(2x+8)+(6x-4) | | abe=126 | | Z+8=(-5) | | 2y-6+y=y-1 | | X^2-21=2x | | N-(-18)=3 | | 61=5v-9 | | C/g=(-2) | | 8x+9x-20=180 | | (-8y)=(-64) | | x+x=3x-10 | | (-8)=(-64) | | 3t+5=-2t-1 | | (-30)=5w | | 2w^2-19w+31=49-4w^2-4 | | -4+4x-5(-3x)=1-2x+4 | | x*ln(x)-4x=0 | | 2x+x+4-10=180 | | 2t=(-64) | | -5y+2=9-8y+16 | | 8x-3=8.5 | | -x^2+27=-6x |

Equations solver categories